Commercial history of Dhaka - Hassan, Delwar; Dacca Chamber of Commerce & Industry; International Finance Corporation. Bangladesh Investment Climate Fund. (Dhaka : Dhaka Chamber of Commerce and Industry, 2008)
Published on the occasion of the golden jubilee celebrations of Dacca Chamber of Commerc & Industry; contributed articles; covers the period, 17th to 20th century; publication is supported by IFC Bangladesh Investment Climate Fund.
Includes bibliographical references and index.
Keywords: Dhaka (Bangladesh) -- Commerce -- History; Dhaka (Bangladesh) -- Economic conditions